2000
DOI: 10.1111/j.1432-2277.2000.tb01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-related disease and risk of acute rejection in renal transplant recipients: a cohort study with case-control analyses

Abstract: The relationship between a cytomegalovirus (CMV) infection and the acute rejection of a renal transplant is not well established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Reducing immunosuppression as part of the therapy of CMV disease further predisposes patients to the onset of AR. Consistent with our study, a number of authors have demonstrated that CMV disease increases the risk for AR in post-RTx patients (Sagedal et al, 2002;Toupance et al, 2000. However, data regarding asymptomatic CMV infection are inconsistent (Dickenmann et al, 2001;Sagedal et al, 2002;Toupance et al, 2000). The difference demonstrated here between the asymptomatic CMV infection and CMV disease on AR may be due to the lower viral load in asymptomatic infections (Emery et al, 2000;Piiparinen et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Reducing immunosuppression as part of the therapy of CMV disease further predisposes patients to the onset of AR. Consistent with our study, a number of authors have demonstrated that CMV disease increases the risk for AR in post-RTx patients (Sagedal et al, 2002;Toupance et al, 2000. However, data regarding asymptomatic CMV infection are inconsistent (Dickenmann et al, 2001;Sagedal et al, 2002;Toupance et al, 2000). The difference demonstrated here between the asymptomatic CMV infection and CMV disease on AR may be due to the lower viral load in asymptomatic infections (Emery et al, 2000;Piiparinen et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…A number of questions remain to be answered in evaluating CMV as a risk factor for AR. While CMV disease is associated with an increased incidence of AR (Sagedal et al, 2002;Toupance et al, 2000), data regarding the role of asymptomatic CMV infection are controversial (Dickenmann et al, 2001;Sagedal et al, 2002;Toupance et al, 2000). The CMV prophylaxis in current use leads not only to a decreased incidence, but also to a delay in the onset of CMV infection and disease (Brennan et al, 1997;Lowance et al, 1999;Paya et al, 2004;Reischig et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…From our analysis, each CMV infection resulted in an additional €4,149 in costs per year. CMV not only presents its own medical hazards but also increases the risk of acute rejection and graft failure (24,25). The economic impact of CMV infection on renal transplantation has been determined to be significant, because it results in extended hospitalization and more than a doubling of costs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Infection with CMV has been associated with early-onset allograft rejection in renal transplant recipients [24,25]. CMV-induced tubulointerstitial disease occurring after kidney transplantation has been reported elsewhere [26].…”
Section: Longitudinal Study Of Herpesviruses In Kidney Transplant Recmentioning
confidence: 99%